UJI VALIDITAS LEMBAR KERJA MAHASISWA BERBASIS PENEMUAN TERBIMBING MATERI PARABOLA PADA MATA KULIAH GEOMETRI ANALITIK BIDANG DAN RUANG (Universitas PGRI Sumatera Barat, 2023)
The current Covid-19 outbreak that is happening in the world has changed face-to-face learning to online learning. In addition, the ability to understand lecture material must be obtained by students independently, not only from lecturers. For this reason, it is necessary to develop qualified teaching materials so that lecture activities continue to run well, one of which is in the form of guided discovery-based Student Worksheets (LKM).Â The purpose of this study was to determine the level of validity of the developed product. This development research uses the Mc Kenny development model with the Preliminary, Prototyping and assessment stages. The subjects of this study were 3rd semester students of the Mathematics Education Study Program at IAIN Bukittinggi. The product validity was validated by 5 validators.Â The results showed that the product developed had met the valid criteria from the didactic aspect, content, language and presentation. Based on these results, it can be concluded that the products that have been produced can be declared valid, practical and effective.Â